Climate-smart agriculture: Adapting to a changing climate for sustainable food production" - Ali, Muhammad Qasim (Federation of German Scientists (VDW), 2023)
Fighting hunger ranks among the most difficult tasks of our period. This endeavour is further complicated by the impact of climate change, which is progressively influencing primary food production and broader food systems. Simultaneously, the agriculture and land use sectors significantly contribute to the overall green-house gas emissions on a global scale. The capacity of our natural resources to sustain future populations'food needs, particularly in the year 2050. It assesses global land use, water use, and fertilizer use for var-ious dietary scenarios. The findings underscore the pressing need for substantial agricultural develop-ment to meet future food demands (Odegard & van der Voet, 2014).